Telerehabilitation is non-inferior to usual care following total hip replacement — a randomized controlled non-inferiority trial. Issue Volume 107:Issue (2020) (June 2020) - Nelson, M.; Bourke, M.; Crossley, K.; Russell, T.
Abstract: Objectives: Determine if outpatient physiotherapy care via telerehabilitation is as effective as in-person physiotherapy care after total hip replacement. Design: Randomised, single-blind, controlled, non-inferiority clinical trial. Setting: QEII Jubilee Hospital, Brisbane, Australia. Participants: Seventy patients receiving a total hip replacement entered the study, sixty-nine completed the study. Interventions: The control group ( n = 35; x ¯ age 67; female 60%) received in-person outpatient physiotherapy and a paper-based home exercise programme. The intervention group ( n = 35; x ¯ age 62; female 66%) received remotely delivered telerehabilitation directly into their homes and a technology-based home exercise program using an iPad application. Main outcome measures: The primary outcome was the quality of life subscale of the Hip disability and Osteoarthritis Outcome Score measured at six weeks post-operatively. Secondary outcomes included objective strength and balance outcomes, self-reported function and satisfaction outcomes, and home exercise program compliance. Results: No between group difference was detected in the Hip disability and Osteoarthritis Outcome Score quality of life subscale at the primary end point of six weeks ( P = 0.970). Strength, balance and self-reported function showed no between group differences. Overall satisfaction was high across both groups, with the intervention group scoring higher for ease of attending appointments (intervention 95 (10), control 86 (18), mean difference 9 (95% CI 2 to 16), P = 0.017. The intervention group were more compliant with their home exercise programme (intervention 86% (20%), control 74% (26%), mean difference 12% (95% CI 1% to 23%), P = 0.048). Conclusions: Telerehabilitation programmes can be delivered to total hip replacement patients in their own homes, using readily available technology while maintaining high levels of satisfaction. More importantly, telerehabilitation patients appear to achieve non-inferior physical and functional outcomes as those receiving in-person rehabilitation programmes. Trial Registration: : ACTRN12615000824561. (Australian New Zealand Clinical Trials Registry).